Efficacy of magnesium sulphate and/or fentanyl as adjuvants to intrathecal low-dose bupivacaine in parturients undergoing elective caesarean section - Shelly Rana; Dheeraj Singha; Sudarshan Kumar; Yuvraj Singh; Jai Singh; R K Verma (Wolters Kluwer Medknow Publications, 2017)
Background and Aim: Recent developments in the field of intrathecal adjuvants have led to accelerated functional recovery with adequate postoperative analgesia following caesarean section. Encouraging results have been obtained with the use of intrathecal magnesium with or without fentanyl in parturients. This study was conceived to evaluate the effects of adding magnesium sulphate and/or fentanyl to low-dose intrathecal bupivacaine in parturients undergoing caesarean section under subarachnoid block (SAB). Materials and Methods: Ninety, American Society of Anesthesiologists I or II, parturients for the elective caesarean section were enrolled in this prospective randomized, double-blind study. The parturients were randomly assigned to three groups. In Group M, parturients received 8.5 mg (1.7 mL) hyperbaric bupivacaine 0.5% with 50 mg (0.1 mL) magnesium sulphate and 0.4 mL normal saline. Group F received 8.5 mg hyperbaric bupivacaine 0.5% with 20 μg (0.4 mL) fentanyl and 0.1 mL of normal saline and Group MF parturients received 8.5 mg hyperbaric bupivacaine 0.5% with 20 μg fentanyl added to 50 mg magnesium sulphate. Results: Parturients in the group MF were pain free for longest period (273.70 ± 49.30 min) as compared to group M (252.67 ± 40.76 min) and group F (239.80 ± 38.45 mins) [gp MF vs F and, gp M vs F (P = 0.00)]. The total doses of rescue analgesics were least in group MF (2.43 ± 0.56) and maximum in group F (3.30 ± 0.63), with comparable neonatal outcomes in three groups. Conclusion: Our data supports synergistic action of intrathecal magnesium sulphate to fentanyl, and it is concluded that on addition of intrathecal magnesium sulphate and fentanyl to low-dose bupivacaine as adjuvant in subarachnoid block, results in prolonged duration of postoperative analgesia with lesser pain scores and lesser dose of rescue analgesia with better haemodynamic stability.